2008
DOI: 10.1007/s10570-008-9245-1
|View full text |Cite
|
Sign up to set email alerts
|

Degrees of polymerization (DP) and DP distribution of cellouronic acids prepared from alkali-treated celluloses and ball-milled native celluloses by TEMPO-mediated oxidation

Abstract: Various cellulose II samples, ball-milled native celluloses and ball-milled wood saw dust were subjected to 2,2,6,6-tetramethypyperidine-1-oxyl radical (TEMPO)-mediated oxidation to prepare cellouronic acid Na salts (CUAs). The TEMPO-oxidized products obtained were analyzed by 13 C-NMR and size-exclusion chromatography (SEC). When the cellulose II samples with degrees of polymerization (DP) of 220-680 were used as the starting materials, the CUAs obtained had weight-average DP (DPw) values of only 38-79. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 24 publications
0
50
0
1
Order By: Relevance
“…3j). Further support comes from the literature (Teeaar et al 1987;Hulleman et al 1994;Stubičar et al 1998;Isogai et al 2009) wherein the peak position in completely amorphous cellulose is reported to be 20-21°and not 18°(as Segal et al 1959 reported). Although not clear why this is the case, the finding of the higher 2h value may possibly result from the Fig.…”
Section: Ball Milled Samplesmentioning
confidence: 77%
“…3j). Further support comes from the literature (Teeaar et al 1987;Hulleman et al 1994;Stubičar et al 1998;Isogai et al 2009) wherein the peak position in completely amorphous cellulose is reported to be 20-21°and not 18°(as Segal et al 1959 reported). Although not clear why this is the case, the finding of the higher 2h value may possibly result from the Fig.…”
Section: Ball Milled Samplesmentioning
confidence: 77%
“…Preparation of cellouronic acid (CUA) CUA was prepared from regenerated cellulose by the TEMPO/NaBr/NaClO system at pH 10 according to the reported method (Isogai and Kato 1998;Isogai et al 2009). Regenerated cellulose (1 g) was suspended in water (100 mL) at pH 10 containing TEMPO (0.025 g, 0.16 mmol) and NaBr (0.25 g, 2.4 mmol).…”
Section: Methodsmentioning
confidence: 99%
“…When 2,2,6,6-tetramethylpiperidinyl-1-oxyl radical (TEMPO)-mediated oxidation with NaBr and NaClO in water at pH 10 is applied to regenerated, mercerized or ball-milled native celluloses, watersoluble polyglucuronates (cellouronic acid Na salts, CUA) are obtained quantitatively (Isogai and Kato 1998;Isogai et al 2009). CUA has mostly homogeneous chemical structures consisting of (1 ?…”
Section: Introductionmentioning
confidence: 99%
“…When the TEMPO/NaBr/NaClO oxidation at pH 9-11 or 4-acetamide-TEMPO/NaClO/NaClO 2 oxidation at pH 4.8-6.8 was applied to regenerated celluloses under proper conditions, water-soluble cellouronic acids were obtained in most cases by regioselective oxidation of C6 primary hydroxyls to carboxylate groups (Isogai and Kato 1998;Isogai et al 2009;Hirota et al 2009a). Because serious depolymerization of cellouronic acids caused by belimination or some active radicals formed as byproducts during TEMPO-mediated oxidation at pH 9-11 (Shibata and Isogai 2003) can be excluded under the oxidation conditions at pH 4.8-6.8, cellouronic acids with higher DPs are obtained quantitatively (Hirota et al 2009a).…”
Section: Introductionmentioning
confidence: 99%